if f(x)= 2x^3 - 13x^3 +17x +12 then,f(-3)=.
Attachments:
![](https://hi-static.z-dn.net/files/d03/046083e820f903fe63f4b877b90ce232.jpg)
Answers
Answered by
1
Answer:
258
Step-by-step explanation:
f(-3)=2(-3)³-13(-3)³+17(-3)+12
=-54+351 -51+12
=297 -39
= 258
i hope it helps u
pls mark me brainlist
Answered by
1
Answer:
Answer is attached here
Attachments:
![](https://hi-static.z-dn.net/files/dc6/3dccdbb5194ce6f2336881fa6a7c266f.jpg)
Similar questions
Hindi,
1 month ago
Psychology,
3 months ago
Math,
11 months ago
Math,
11 months ago
Computer Science,
11 months ago